Pengaruh Gender, Emotional Intelligence, Dan Pengalaman Auditor Terhadap Audit Judgement - Lutfi Fathus Sholihah; Rifqi Muhammad (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This study aimed to examine the effect of Gender, Emotional Intelligence and Audit Experience on Audit Judgement. This kind of study is qualitative research with primary data collected in a questionnaire distributed to 32 respondents. The data is processed with multiple linear regression analysis by using Statistical Program for Social Science (SPSS). The results showed that gender has no effect on audit judgment. Meanwhile, emotional intelligence and auditor experience affect audit judgment.